Argentine Law of International Commercial Arbitration - Cesar Rivera, Julio (2019)
The Argentine Law of International Commercial Arbitration represents a very important milestone in the Argentine Commercial Law, regulating for the first time in a specific way a necessary aspect in the international commercial legal traffic: the arbitration. In this sense, it is necessary to carefully analyze not only the background to this fundamental norm but also every essential and innovative characteristic such as the principles that inspire it, the recusal of arbitrators, the precautionary measures, the arbitration body, among others. In this way, the reader can have a panoramic view that will allow you to know the strengths and weaknesses of the new legal treatment of international commercial arbitration in Argentina.